ANALYSIS OF PERFORMANCE MEASUREMENT OF THE WALAGRI INSAN MANDIRI COOPERATIVE BASED ON THE BALANCED SCORECARD IN 2021 - Kristawati Kristawati; Fika Rahmawati; Icih Icih (STIESA Press, 2023)
This study aims to assess the performance of the Walagri Insan Mandiri Subang Cooperative using the Balanced Scorecard, namely the Financial Perspective, Internal Business Process Perspective, Learning and Growth Perspective, and Customer Perspective. This research method uses a descriptive method with a quantitative research type. Retrieval of data using secondary data. The data collection techniques used in this study were documentation techniques and literature studies by searching for data from the Subang Cooperative Office on the RAT (Annual Meeting of Members) of the Subang Insan Mandiri Cooperative. This analysis uses a research variable, namely Measuring Cooperative Performance. The results of this research show that the performance of the Walagri Insan Mandiri Subang Cooperative, namely the Financial perspective is stated to be healthy, the Internal Business Process perspective is stated to be healthy, the learning and growth perspective is stated to be healthy, and the perspective of customers (members) is stated to be unhealthy indicating that there has been an increase and decrease.